Catalytic pyrolysis of oily sludge with iron-containing waste for production of high-quality oil and H2-rich gas. (15th October 2022) - Lin, Fawei; Zheng, Fa; Li, Jiantao; Sun, Bingyan; Che, Lei; Yan, Beibei; Chen, Guanyi
Highlights: Catalytic pyrolysis of oily sludge was studied with iron-containing waste. The catalytic effects of several dominant minerals in red mud were tested. H2 -rich gas could be produced under the catalysis and red mud worked better. All dominant minerals could improve the oily quality and H2 production. Abstract: Oily sludge (OS), as a kind of organic hazardous waste with complex components, is suitable for treatment by pyrolysis. To attain effective removal of petroleum hydrocarbons and explore synergistic disposal for multi-source solid wastes, the catalytic effects of steel slag (SS) and red mud (RM) were investigated in this work. They could reduce the activation energy, accelerate OS degradation and shift the degradation of petroleum hydrocarbons towards lower temperature. What's more, RM with higher iron content worked better, gained more pyrolytic gas and higher H2 production as well. More pyrolytic gas production was obtained when RM addition was at a low proportion. However, excessive catalyst would play a certain inhibitory role. The addition of RM promoted oil recovery at low temperature (400–500 °C) but brought more gas originating from oil cracking at high temperature (600 °C). At 400 °C, the oil yield elevated continuously with prolonging retention time. Nevertheless, even if the retention time was long enough, the harmless disposal for OS could not be completed with the catalysis of RM. Finally, the pristine minerals in RM were co-pyrolysis with OS individually to explore catalytic contributions. Metal oxides could enhance the gas yield and reduce the oil yield. The order of catalytic capacities was Fe2 O3 ＞CaO＞SiO2 ＞Al2 O3 . Fe2 O3 promoted H2 production and conversion from heavy oil into light fuels. Besides, Fe2 O3 was reduced into Fe3 O4 with part of [O] shifting into oil. CaO, SiO2, and Al2 O3 could reduce the oxygen content in the pyrolytic oil through their acid-base properties to improve the oil quality. This work summarized the functions of various components in RM, might provide inspiration for getting insight into the application of collaborative treatment of different solid wastes.